Perumusan Strategi Pengembangan Industri Kecil Menengah Topeng Malangan - Sunday Noya; Khoirul Hidayat; M Melany (Jurnal Teknik Industri, 2014)
Topeng Malangan is one of potential cultural products developed to preserve culture and bring revenue for stakeholder in Malang. This study aims to identify internal and external factors affecting the existence of small medium enterprise (SME) Topeng Malangan and formulate its development strategy. The identification of problem and factors is done by focus group discussions (FGD) involving businessmen, cultural observer, academician, regional government and researchers. The results of FGD is then analyzed and developed by using SWOT matrix in order to determine formula of SME development strategies. To sharpen the strategy more effective in implementation, the analysis using IFAS and EFAS matrix is conducted. The result is final formula for SME Topeng Malangan development strategy that is more focused on strategy SO (Strength - Opportunities); which is the utilization of strength organization of SME Topeng Malangan for taking advantage of opportunities.